Diagnostic Consequences of Cytomegalovirus Glycoprotein B Polymorphisms - Novak, Zdenek (American Society for Microbiology, 2011)
Failure of a cytomegalovirus (CMV) real-time PCR assay targeting glycoprotein B (gB) was investigated. A multiplex assay targeting gB and immediate-early 2 (IE2) genes showed discordant results (gB negative and IE positive or a >10-fold-higher viral load with IE primers) in saliva from 14.6% of CMV-infected newborns. Sequencing revealed 3 patterns of gB variations.